2015
DOI: 10.1890/14-2443.1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of foundation species on community assembly: a global study on alpine cushion plant communities

Abstract: Foundation species can change plant community structure by modulating important ecological processes such as community assembly, yet this topic is poorly understood. In alpine systems, cushion plants commonly act as foundation species by ameliorating local conditions. Here, we analyze diversity patterns of species' assembly within cushions and in adjacent surrounding open substrates (83 sites across five continents) calculating floristic dissimilarity between replicate plots, and using linear models to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 26 publications
1
62
0
1
Order By: Relevance
“…Such variable effects have been found for alpine cushion plants, which have higher alpha (within-cushion) diversity than adjacent, open microhabitats [10][11][12] but lower beta (between-cushion) diversity [13]. These contrasting effects are thought to arise from creation of "safe sites" for stress-intolerant plants through the local amelioration of stress by cushion plants that simultaneously lead to more homogeneous assemblages on them [13]. In contrast, some perennial kelp species that create complex habitats and provide structure for associated epiphytes have locally negative effects on biodiversity in high stress environments, locally positive effects on biodiversity in less stressful environments, and overall negative effects on biodiversity at larger spatial scales [14].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Such variable effects have been found for alpine cushion plants, which have higher alpha (within-cushion) diversity than adjacent, open microhabitats [10][11][12] but lower beta (between-cushion) diversity [13]. These contrasting effects are thought to arise from creation of "safe sites" for stress-intolerant plants through the local amelioration of stress by cushion plants that simultaneously lead to more homogeneous assemblages on them [13]. In contrast, some perennial kelp species that create complex habitats and provide structure for associated epiphytes have locally negative effects on biodiversity in high stress environments, locally positive effects on biodiversity in less stressful environments, and overall negative effects on biodiversity at larger spatial scales [14].…”
Section: Introductionmentioning
confidence: 78%
“…Alternatively, richness of associated species in an ecosystem defined by a particular foundation species can be greater or less than that of other ecosystems, and the loss of the foundation species could lead either to increased or decreased species richness of the entire associated assemblage [3]. Such variable effects have been found for alpine cushion plants, which have higher alpha (within-cushion) diversity than adjacent, open microhabitats [10][11][12] but lower beta (between-cushion) diversity [13]. These contrasting effects are thought to arise from creation of "safe sites" for stress-intolerant plants through the local amelioration of stress by cushion plants that simultaneously lead to more homogeneous assemblages on them [13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies about cushion plant effects (e.g., Cavieres et al., ; Kikvidze et al., ) have found that the effect of different cushion species on their associated communities was positive and relatively homogeneous (e.g., Cavieres et al., ; Kikvidze et al., ). An important result of our study is that the identity of the nurse species, even when the species belong to the same life form, can generate different outcomes in terms of plant–plant interactions in grazed conditions.…”
Section: Discussionmentioning
confidence: 94%
“…This type of life form has been extensively recognized as nurse for other plants in alpine ecosystems worldwide, through direct facilitation (Cavieres et al., ). In particular, cushion plants increase richness (Cavieres et al., ), β‐diversity (Kikvidze et al., ), and the intensity of facilitation increases with phylogenetic distance (Butterfield et al., ), particularly where local diversity is low. The cushion plants slowly accumulate up to 10–12 m of organic matter mostly in valley bottoms along watercourses (Buttolph & Coppock, ; Cooper et al., ), covering the terrestrial surface in its entirety (i.e., no bare soil).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we combine spatial ecology, network theory and functional traits to reveal the structure of plant networks and the assembly of plant communities. Since facilitation is assumed to be strong in stressful habitats such as alpine vegetation (Callaway et al., ; Kikvidze et al., ; Schöb et al., ) and as it is linked to plant community structure and plant functional traits (Gross et al., ; Schöb et al., ), we tested the hypothesis that (a) positive associations characterize a cohesive plant network; and (b) functional traits can explain the degree of network‐wide species associations.…”
Section: Introductionmentioning
confidence: 99%